Spatio-Temporal Evolution Characteristics of Tourism Ecological Resilience in China - Li Jiang; Xingpeng Chen; Lili Pu; Huaju Xue (Land)
Tourism ecological resilience (TER) is an important indicator of the healthy and sustainable development of the tourism industry, which provides a new analytical perspective for the anti-fragility and tourism ecological security of the tourism industry. This study takes 31 provinces in China as the research area, constructs a comprehensive evaluation index system of TER based on the theory of evolutionary resilience, and uses a comprehensive evaluation index, GIS spatial analysis technology, kernel density estimation, Dagum–Gini coefficient, and other research methods to analyze the spatial and temporal evolution of China’s TER from 2010 to 2022 and the spatial distribution pattern of three dimensions of DPC-ARC-OIC. The results show that (1) In the process of time evolution, the ecological resilience of tourism in China continues to increase, and from 2010 to 2022, China’s TER first increased and then decreased, with an average annual growth rate of 1.47%, among which Yunnan and Jiangxi provinces increased significantly. (2) In the process of spatial evolution, there is an obvious spatial gap in tourism ecological resilience. From 2010 to 2022, China’s TER generally presents a pattern of “high in the east and low in the west, high in the south and low in the north”, forming a hierarchical spatial structure with Beijing and Shanghai as the “dual cores”, decreasing to the periphery. (3) There are obvious spatial differences in the three dimensions of DPC, ARC, and OIC. The DPC of the economically developed regions is higher than that of the economically less developed regions; the ARC fluctuates greatly due to the environmental vulnerability and economic level of the western region, and the OIC, as a whole, rises and presents a multi-polar distribution. (4) The overall difference in China’s TER fluctuates and increases, and regional differences have always been dominant, so it is necessary to take systematic measures according to local conditions to help improve the resilience of the tourism ecosystem and the sustainable development of regional tourism. This study can enrich the theoretical research of TER, but it mainly uses provincial macro data for analysis. It still needs to be strengthened to depict regional heterogeneity characteristics to provide Chinese practice for studying TER.